PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INSTANT ASSESSMENT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI IPA SMA NEGERI 1 KAMPAR - Aldresti, Fitri; Miharty, Miharty; Herdini, Herdini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to increase student achievementon the subject ofsolubility and solubility productinclassXI IPA SMA N 1 Kampar. This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMA N 1 Kampar.The samples of this research were the students of class Xl IPA 1 as the control class and students of class XI IPA 2 as the experimental class.Experimental class is a class that is applied active learning strategy instant assessment, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 2,49 > 1,67, means that the application of active learning strategy instant assessment can improve student achievement on the subject of solubility and solubility product constant in class XI Science SMAN 1 Kampar where the effect of an increase is 9,97%.Keywords :Active Learning Strategy Instant Assessment, Learning Achievement, and Solubility and Solubility Product Constant